2019
DOI: 10.1096/fasebj.2019.33.1_supplement.515.16
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning to Predict the Development of Diabetes and Potential Biomarkers Linked to Cardiac Risk

Abstract: BackgroundDiabetes mellitus is a chronic, debilitating disease that continues to affect a greater percentage of people each year. Among its systemic comorbidities, diabetics are two to four times more likely to develop cardiovascular diseases. While glycosylated hemoglobin (HbA1c) remains the primary diagnostic for diabetes mellitus onset, predicting health outcomes through a single measure is difficult, with disparities existing between ethnic and demographic groups. The purpose of this study was to use machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Application of machine learning to identify novel cardiac biomarkers reveals that total nuclear methylation and methylation in a specific CpG island of TFAM were the best diagnostic measures related to diabetes progression (118). Also this study support the theory that epigenetics and mitoepigenetics are two processes interconnected.…”
Section: Future Perspectives Of Mitoepigenetics In Treatmentsupporting
confidence: 73%
“…Application of machine learning to identify novel cardiac biomarkers reveals that total nuclear methylation and methylation in a specific CpG island of TFAM were the best diagnostic measures related to diabetes progression (118). Also this study support the theory that epigenetics and mitoepigenetics are two processes interconnected.…”
Section: Future Perspectives Of Mitoepigenetics In Treatmentsupporting
confidence: 73%
“…For patients with severe COVID-19 intubation, Fleuren et al applied the SHAP and found predictors of extubation failure, including ventilatory settings, inflammatory parameters, neurological status, and BMI (51). Hathaway et al (52) conducted supervised learning through SHAP by identifying the most relevant and novel cardiac biomarkers for forecasting diabetes mellitus development, and discovered that this approach may be a potential guideline for investigating disease pathogenesis and discovering novel biomarkers in the future. For predicting infant autopsy outcome, Booth et al used three models for model training, including decision tree, RF, and gradient boosting.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, because the dataset is inherently predictive, when the sample size is small, models may face challenges. One of these challenges is the high sensitivity to outliers, which may overly emphasize anomalies in the samples, leading the ML model to believe that these outliers have a greater impact (52). Due to limitations in the dataset, the model may overfit to the training data, especially when using derived models like classification trees.…”
Section: Discussionmentioning
confidence: 99%